PEMBUATAN DAN UJI AKTIVITAS SEDIAAN GEL SCARLESS WOUND DENGAN EKSTRAK BINAHONG DAN ZAT AKTIF IBUPROFEN - Prita Patricia; Sri Hartati Yuliani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2015)
Wound is a condition where the tissue was damaged. The body will repair this damage by wound healing mechanism which often leads to the formation of scar. The scar is caused by the inflammation phase of wound healing mechanism. Ibuprofen is one of the antiinflammatory agent that can inhibit or shorten the inflammatory phase by inhibit cyclooxygenase enzyme in prostaglandin synthesize. Prostaglandin has an important role on the formation of inflammatory phase. Binahong (Anredera cordifolia (Ten.) Steenis.) has a potential activity as a wound healing agent. Binahong contains ascorbic acid which is impotant for the activation of prolyl-hydroxygenase enzyme that support hydroxylation phase in the process of collagen formation, so that the wound healing process can be acceletared. In this research, a gel preparation with binahong extract was combined with ibuprofen to form a scarless wound gel. This research was purely experimental. The test method used is a histopahological test which continued with a calculation of collagen area and a physical properties test. The collagen area calculation data were analyzed by independent sample t-test with 95% confidence interval. In this research, the addition of ibuprofen was expected to reduce the scar formation on incisional wound of white Swiss Webster mice. The result showed that the gel preparation with binahong extract and ibuprofen formed statistically less scar when compared to the gel preparation with binahong extract only.